Water exercise and health promotion - Sho Onodera; Akira Yoshioka; Kazuki Nishimura; Hiroshi Kawano; Kumiko Ono; Takeshi Matsui; Futoshi Ogita; Hideki Hara (Japanese Society of Physical Fitness and Sports Medicine, 2013)
During water exercise, it was established that heart rate, oxygen uptake and body temperature respond to the influence of water pressure, temperature, buoyancy, and viscosity. This review explains the principle and theory that physiological response could become a benefit of health promotion. The heart rate during water immersion is lower than on land. The blood pressure of young subjects in water is much lower than on land at thermo-neutral conditions, while for old subjects it is higher than on land. Blood pressure increases in water with age due to an age-associated reduction in vascular dispensability. Water pressure and vascular elasticity can affect systolic blood pressure. Capillary vessels expand after exercise in water. When the water level is increased, the volume of the venous return seems to increase; and when the water level decreases, the volume of the venous return decreases. The change in volume of venous return depends on exercise intensity. Physiological indexes apparently change with water temperature to even higher and lower levels than the thermo-neutral. Depending on the viscosity of the water, the oxygen consumption changes. Depending on the water level, the load weight changes. Depending on the exercise movement speed, the oxygen consumption changes. The physical characteristics of water could provide an index and a big benefit for health promotion. In addition, one can expect water exercise to have a beneficial preventive effect on lifestyle-related diseases such as obesity and diabetes.